Development and application of SSR markers derived from Bauhinia Strychnifolia a semi-endemic plant in Thailand. Issue 4 (2nd October 2018) - Sraphet, Supajit; Chantravisut, Pattra; Srisawad, Nattaya; Suksee, Nawarat; Smith, Duncan R.; Triwitayakorn, Kanokporn
ABSTRACT: Bauhinia strychnifolia is a rare and semi-endemic plant in Thailand. Microsatellite-enriched libraries were constructed using (CT)15 /(CAG)15 and (GT)15 /(AAG)15 probes. Fourteen polymorphic loci produced a total of 104 alleles with a mean of 7.4 alleles per locus. The average expected and observed heterozygosity were 0.727 and 0.497, respectively. The polymorphism information content value ranged from 0.335 to 0.910. Nine microsatellite loci were successfully transferred across species to B. galpiniii, B. Siamensis, and B. tomentosa . The information obtained in this study will be useful in establishing a conservation strategy for B. strychnifolia in Thailand and for genetic studies of other Bauhinia sp.